2013
DOI: 10.1016/j.cub.2013.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Volitional Control of Neural Activity Relies on the Natural Motor Repertoire

Abstract: Summary Background The results from recent brain machine interface (BMI) studies suggest that it may be more efficient to use simple arbitrary relationships between individual neuron activity and BMI movements than the complex relationship observed between neuron activity and natural movements. This idea is based on the assumption that individual neurons can be conditioned independently regardless of their natural movement association. Results We tested this assumption in the parietal reach region (PRR), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
85
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(102 citation statements)
references
References 35 publications
15
85
2
Order By: Relevance
“…In addition to the inputs associated with the global reward signal, cortical neurons receive strong synaptic inputs from surrounding neurons. Consistent with this, non-target neurons whose activity is highly correlated with that of the target neuron tend to change their firing rate with the target neuron 9,10 . However, individual neurons recorded from the same electrode can be separately controlled in SNOC 2,3,9,11 .…”
supporting
confidence: 52%
“…In addition to the inputs associated with the global reward signal, cortical neurons receive strong synaptic inputs from surrounding neurons. Consistent with this, non-target neurons whose activity is highly correlated with that of the target neuron tend to change their firing rate with the target neuron 9,10 . However, individual neurons recorded from the same electrode can be separately controlled in SNOC 2,3,9,11 .…”
supporting
confidence: 52%
“…Previous studies have shown that there are two general categories of learning mechanism for single neurons in BMIs (18). For an individual neuron mechanism, each neuron is separately manipulated to produce a particular response pattern independent of the activity of its neighbors.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the BMI application induced learning-related changes in the saccade system. Learning can produce changes in reach areas, but how learning-related changes occur at the level of LIP neuronal ensembles is still unclear (17,18).Here, we show that the intended eye movement activity can be used to accurately position a cursor on a computer screen. These results suggest that an eye movement BMI can be used as a prosthetic to assist locked-in patients who cannot produce eye movements.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Several of these central areas are thought to form and anticipate a reliable motor percept (Hauschild et al 2012;Kawato and Wolpert 1998;Mulliken et al 2008;Wolpert et al 1998), even in the absence of active efferent commands from ongoing movements ). In particular, in the parietal areas, the separation between sensory input and abstract planning has been demonstrated across several contexts (Andersen and Buneo 2002;Hwang et al 2013;Torres et al 2013c). Based on this prior research, we examine here velocity-dependent parameters from the continuous flow of natural, unconstrained hand motions.…”
mentioning
confidence: 99%